The Application of the Small Group Discussion Method in Improving the Understanding of Class X Students of Darunnajah High School on the Hadith Prohibiting Denouncing Fellow Muslims - Yogi Fery Hidayat (Universitas Darunnajah Jakarta, Indonesia, 2024)
Bullying, Sexual Violence, and Intolerance are significant challenges in the Indonesian education system, despite efforts by the Ministry of Education to address them. This study focuses on the application of the Small Group Discussion method to enhance students' understanding of the Hadith prohibiting the disparagement of fellow Muslims at SMA Darunnajah Jakarta. The research employs a classroom action research design with a one-group pretest-posttest method to measure the effectiveness of the intervention. The study was conducted in two cycles: in the first cycle, students used conventional methods, resulting in 45.83% of students achieving the Minimum Completeness Criteria (KKM). After evaluation, improvements were made by implementing the Small Group Discussion method in the second cycle, which involved small group discussions to increase student engagement and understanding. The results showed a significant improvement, with 83.33% of students achieving the KKM after the intervention. These findings indicate that the Small Group Discussion method is more effective in enhancing students' understanding of Hadith compared to conventional methods. The study suggests integrating small group discussion methods into teaching to facilitate understanding of religious concepts and moral values in educational settings.